DIABETES MELLITUS: A REVIEW WITH EDGE OF SGLT2 INHIBITORS - Singh, Ranjodh Jeet; Gupta, Ashwani Kumar; Kohli, Kanika (International Journal of Current Pharmaceutical Research, 2018)
The relative (Type 2 DM) or absolute (Type 1 DM) deficiency of insulin hormone could result into hyperglycemia, which is a characteristic feature of diabetes mellitus. Diabetes mellitus is a leading cause of morbidity and mortality because of its associated complications viz. Neuropathy, Nephropathy, Retinopathy, Cardiovascular disorders. The feature which has to be noted down is the death of individuals before the age of 70 y, which is attributable to high blood glucose levels. According to WHO diabetes mellitus will be the seventh leading cause of deaths till 2030. The induction of glycosuria as meant for glyÂcaemiac control in patients with DM is an extension of the physiological role of renal TmG to curb the menace of hyperglycemia. The first biologically derived SGLT2 inhibitor phlorizin, isolated in 1835 from the root bark of apple tree, was not developed as an antihyperglycaemic drug because of rapid degradation by lactase-phlorizin hydrolase and poor absorption from the gastrointestinal tract. Other glycoside moieties derived from phlorizin strucÂture have subsequently been developed recently.